Cyberbullying: A concept analysis of defining attributes and additional influencing factors. (September 2018) - Peter, Ira-Katharina; Petermann, Franz
Abstract: Cyberbullying is an important phenomenon but to date there exists no universally accepted definition. This leads to a variety of Definitions and conceptualizations, making it almost impossible to generalize their results. The purposes of this paper are 1) to present the current state of definitions, 2) to define cyberbullying based on a concept analysis), 3) to illustrate relationships between defining attributes and other possible influencing factors, and 4) to discuss which characteristics should be considered in the valuation of a cyberbullying incident. Therefore, definitions that emerged between 2012 and 2017 were analyzed. A systematic literature search resulted in 24 definitions for qualitative synthesis. Descriptive analysis revealed five defining attributes of cyberbullying that were shared across all identified definitions. Overall, 15 characteristics were determined to describe the phenomenon. A definition is proposed, and additional influencing factors are discussed. Our results suggest that there exist five main defining attributes of cyberbullying which a variety of researchers use to define cyberbullying. Future research should conduct more qualitative studies with adolescents in order to validate these attributes. If researchers and adolescents share the same understanding, the proposed definition can be used in future studies, making their findings more comparable to each other. Highlights: 24 current definitions of cyberbullying are presented. 5 defining attributes are determined. A definition of cyberbullying is proposed. 15 attributes to describe cyberbullying are identified an discussed. Interactions of attributes are demonstrated in a classification scheme.